Chest wall reconstruction with latissimus dorsi and an autologous thoracolumbar fascia graft in a dog. (16th September 2014) - de Battisti, A.; Polton, G.; de Vries, M.; Friend, E.
<x xml:space="preserve">Abstract</x> A new technique for autogenous chest wall reconstruction using a latissimus dorsi muscle flap and a free graft of thoracolumbar fascia was utilised in a two‐year‐old Dobermann after resection of a high‐grade osteosarcoma from the left thoracic wall. En bloc excision of the chest wall mass, including six ribs, was performed. The resulting chest wall defect was too large to be reconstructed with only a pedicled muscle flap and was reconstructed with a latissimus dorsi muscle flap cranially and a free graft of thoracolumbar fascia caudally. The graft was harvested easily, and there was no donor site morbidity or postoperative complications. A free graft of thoracolumbar fascia can be considered as an option to supplement autogenous reconstruction of the chest wall.